Factors influencing international beer trade - Jantyik Lili; Török Áron; Jámbor Attila (University of Szeged, Faculty of Agriculture Szeged, 2019)
Beer has been presenting in human life for a long time. The oldest written proof of beer production, the “Monument Bleu”, comes from Mesopotamia, the 3rd millennium BC and by this time brewing was regulated by law (Ulischberger, 1982). Nowadays, globalization liberates the markets and large brewing companies achieve tremendous growth. In 2016, trade value of beer made from malt was 13,8 billion USD, according to the UNComtrade (2019) data. The main exporter was Mexico with 27% share in total beer export, followed by three EU beer producers: Netherlands, Belgium and Germany with shares of 14%, 11% and 9%, respectively. On the other side, beer import was even more concentrated: the USA represented 35% of global beer import, followed by France and the United Kingdom (5-5%), China (4.5%) and Italy (4.3%). In case of beer, domestic consumption largely determines the industry, because the largest producers are not the top exporters. Based on FAO (2019) data, in 2014, 28% of global beer production was brewed in China, followed by the USA (the biggest importer - 13%), and 8% was produced in Brazil. Germany and Mexico, the two main exporters, only had 5-5% of market shares in terms of global beer production. In our study we measured competitiveness using the index of Symmetric Revealed Comparative Advantage (SRCA), calculated for all countries exporting beer in the period of 1988-2017. In order to identify factors influencing SRCA, we applied panel-data linear models by using feasible generalized least squares (FGLS). We used the following independent variables for the model: barley production, FDI (foreign direct investment) levels, population, per capita GDP, per capita beer consumption, beer export unit value, number of beers with geographical indications, EU membership (as a dummy variable) and beer production.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok